2016
DOI: 10.1371/journal.pone.0155525
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Isoniazid Preventive Therapy among Under-Five Children: TB Contact Investigation as an Entry Point

Abstract: A child’s risk of developing tuberculosis (TB) can be reduced by nearly 60% with administration of 6 months course of isoniazid preventive therapy (IPT). However, uptake of IPT by national TB programs is low, and IPT delivery is a challenge in many resource-limited high TB-burden settings. Routinely collected program data was analyzed to determine the coverage and outcome of implementation of IPT for eligible under-five year old children in 28 health facilities in two regions of Ethiopia. A total of 504 index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 26 publications
5
41
6
Order By: Relevance
“…24 The higher IPT uptake could be due to the fact that the study recruited adults (≥18 years) rather than children as is the case in our study. Additionally, as compared to our study, a slightly higher IPT initiation rate was reported in South Africa and Ethiopia where initiation of IPT was done in 68% 25 and 64% 26 of the children who were eligible for IPT, respectively. On the other hand, the uptake of IPT in our study was higher than the 37% reported in Ethiopia, 27 33% rate in southern India, 28 the 18% demonstrated in Timor-Leste, 29 the 6% reported in a Malawian study 30 and 22% in Bhopal, India.…”
Section: Discussioncontrasting
confidence: 74%
“…24 The higher IPT uptake could be due to the fact that the study recruited adults (≥18 years) rather than children as is the case in our study. Additionally, as compared to our study, a slightly higher IPT initiation rate was reported in South Africa and Ethiopia where initiation of IPT was done in 68% 25 and 64% 26 of the children who were eligible for IPT, respectively. On the other hand, the uptake of IPT in our study was higher than the 37% reported in Ethiopia, 27 33% rate in southern India, 28 the 18% demonstrated in Timor-Leste, 29 the 6% reported in a Malawian study 30 and 22% in Bhopal, India.…”
Section: Discussioncontrasting
confidence: 74%
“…Among the clients who did not complete IPT in the recommended period of six months, 96.2% discontinued IPT within the first three months of initiation. This is consistent with findings from Malawi, Zimbabwe and Ethiopia, which showed of those who stopped, 85%, 89% and 89% respectively stopped in the first month (32,48,49). Patients may be discouraged by the long treatment duration of IPT and the need to attend clinic every month (32,48,49).…”
Section: Discussionsupporting
confidence: 89%
“…One-third of the IPT-eligible childrenthose who were screened and found not to have presumptive TBwere started on therapy. This is lower than proportions reported from studies conducted in Ethiopia (64.3%) 15 and South Africa (68.0%), 16 but higher than what has been observed in Malawi (6.0%). 13 Possible reasons for low IPT uptake in the study area included the limited availability of documentation tools during the study period, which negatively affected the national TB programme's ability to monitor IPT implementation.…”
Section: Discussioncontrasting
confidence: 70%